God is Light and Living in the Light: Reading 1 John 1-2 in Light of Discourse Analysis - Gunawan, Chandra (Verbum Christi: Jurnal Teologi Reformed Injili, 2017)
The notion that "God is light" is essential to the understanding of the literary structure of 1 John because it links units of thought in the Epistle. This central idea and its ethical implications, "living in the light" and "living in love," develop throughout the letter. To understand the function of this concept and to grasp its meaning in 1 John, the present study utilizes discourse analysis to read the document in light of its micro and macro structures. Interpreting the "God is light" teaching in the Epistle-based on its literary structure-will shed some light on understanding the main issue addressed in 1 John.?